2007
DOI: 10.1590/s1519-69842007000400004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between invertebrate fauna and bromeliad size

Abstract: Several bromeliads species store water and organic substrates, allowing the establishment of phytotelmata and associated fauna on their leaves. In this study, we sampled 70 individuals of Vriesea sp. (Carrière) (Bromeliaceae), in rupestrian fields in the Serra de Ouro Branco-MG, Brazil. The relationships between invertebrate species richness and abundance and size of bromeliads were tested using multiple regression. We found 19 species associated with bromeliads, mainly Diptera larvae. The abundance of the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
2
22
1
8
Order By: Relevance
“…In general, the composition of invertebrates found in this study was similar to those found in other studies investigating the fauna of bromeliads in different regions of Brazil (Lopez 1998, Araújo et al 2007, Marques et al 2008, Sodré 2010. This result corroborates Mestre et al (2000), who indicated the possible existence of a characteristic bromeliad fauna associated with these plants, permanent and transitory, but with a predominance of some groups adapted to changes in the chemical composition and input of nutrients to the bromeliads (Schuttz et al 2012).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In general, the composition of invertebrates found in this study was similar to those found in other studies investigating the fauna of bromeliads in different regions of Brazil (Lopez 1998, Araújo et al 2007, Marques et al 2008, Sodré 2010. This result corroborates Mestre et al (2000), who indicated the possible existence of a characteristic bromeliad fauna associated with these plants, permanent and transitory, but with a predominance of some groups adapted to changes in the chemical composition and input of nutrients to the bromeliads (Schuttz et al 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Among the insects collected, the majority belonged to the sub-order Nematocera (Diptera), which is associated with moist environments (Grimaldi & Engel, 2005) because their reproduction depends on the availability of water reservoirs for larval development. Culicidae was the most abundant family in all the bromeliads, corroborating the findings of Hilsenhoff (1991), Araújo et al (2007), and Parker et al (2012), all of whom observed this family, along with the Chironomidae, to be among the most abundant phytotelma insects. In this study, Chironomidae was represented mainly by the sub-family Tanypodinae, a result that differs from that reported by Sodré (2010) in Atlantic Forest areas of Rio de Janeiro.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, bromeliad structure has only been related to the invertebrate community associated with bromeliads (Richardson, 1999;Armbruster et al, 2002;Araújo et al, 2007), vertebrate species (Cruz-Ruiz et al, 2012), the amount of water (Zotz and Vera, 1999), prey vulnerability (Saha et al, 2009), and detrital processing (Srivastava, 2006). In this study, we evaluated the relationship between bromeliad structure and the amount of litter retained, and built a model to predict leaf litter capture using measures of plant structure in Tillandsia turneri Baker 1888.…”
Section: Introductionmentioning
confidence: 99%
“…As plantas da família Bromeliaceae destacam-se, principalmente, pela presença nas axilas das folhas de abrigos conhecidos como cisterna ou tanque que acumulam água, aonde são encontradas comunidades aquáticas conhecidas por fitotelmata que contém inúmeros organismos responsáveis pela degradação da matéria orgânica ali depositada (Araújo et al 2007). São encontrados em meio à flora epifítica anelídeos e ostracodermos (Lopez et al 2005), aranhas (Romero 2006), girinos, lagartos e cobras (Benzing 1990) e aves (Nadkarni & Matelson 1989).…”
unclassified